Konsumsi Ikan Asin dan Daging Asap dengan Kejadian Karsinoma Nasofaring - Muslim Kasim; Tan’im Tan’im; Upik Pebriyani; Eva Aprillya (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: The dominant factor in the onset of nasopharyngeal carcinoma is that of the Mongoloid race with the habit of consuming salty fish and food preserved by one of the bacon. Purpose: To know the relationship between the consumption of salted fish and smoked meats with the incidence of nasopharyngeal carcinoma. Methode: This research method is observational analytic and uses a cross-sectional approach. The samples in this study were all patients diagnosed with nasopharyngeal carcinoma recorded which corresponds to the inclusion Criteria amounting to 52 persons. The sampling techniques in this study used the total sampling technique. Analysis of data using univariate analysis and bivariate analysis using the chi-square test. Results: frequency distribution characteristic of the nasopharyngeal carcinoma patient majority of male gender at 64.4%, the highest majority in the age group 46-55 years by 32.7%, the most work is farmers Of 32.7%. There is a significant connection between the consumption of salted fish and the occurrence of nasopharyngeal carcinoma (p:0.003) and there is a significant link between the consumption of smoked meats and the incidence of nasopharyngeal carcinoma (p:0.003). Conclusion: There is a significant link between the consumption of fish and smoked meats with the incidence of nasopharyngeal carcinoma.